The geographies of securitisation and credit scoring - Wainwright, Thomas A. (2009)
This thesis draws upon contemporary research in economic geography and the social sciences to explore the spatial relationships that exist between residential mortgage lenders, investment banks and investors and the subsequent geographies that are produced through these intertwined networks. The research is informed through empirical material collected through semi-structured interviews with directors and associates working in the financial sector to see how consumer mortgages are produced and restructured into debt securities. There is a particular focus on how the UK financial sector has undergone restructuring, as a consequence of the politics of financialisation since the 1990s, which aligned the residential mortgage market with the circuits of international capital. The thesis examines three areas of banking and finance to comprehend how retail mortgages have become embedded within international finance. First, the thesis explores how deregulation in the UK initiated a spatial reorganisation of mortgage production networks and funding. Second, the research investigates the migration and adoption of automated decision-making technologies, highlighting how these devices have reshaped the geographies of banking, and are inherently geographical themselves. Third, the thesis focuses on how mortgages are (re)engineered into debt-securities, with a particular focus on how geography is used to mitigate credit and tax risks. It is argued that the restructuring of the UK retail sector and its increased integration with the international circuits of capital exacerbated the exposure of the UK’s economy to the effects of the international credit crunch. Furthermore, the thesis underlines the effect of geography which has shaped the adoption, of new financial technologies and strategies, through local regulations, epistemic cultures and histories.